Hate speech in Turkish media: The example of Charlie Hebdo attack’s - FERIHAN POLAT; OZLEM OZDESIM SUBAY; AHU SINEM ULUTURK (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The attacks on the French satirical magazine on January 7, 2015, over caricatures of the Prophet Mohammad and other Islamic figures are discussed in this paper. The study’s goal is to assess how journalists feel about whether caricature constitutes hate speech or free expression.Method: The goal has been reached through an analysis of columns published in the top five daily Turkish newspapers in terms of circulation during the first six months after the massacre that claimed the lives of twelve people. Before diving into the columnists’ responses, we first analyse the larger context of this discussion, including how hate speech is defined, who it is directed at, and how it relates to free speech.Findings: The language used in the mainstream media was not found to be severe enough to increase prejudice and discrimination in this study. Many newspapers published columns that emphasised free speech and peace within the first six months after the Charlie Hebdo attack. The study’s findings show that the media outlets reported controversial topics by favouring one political viewpoint over another.Implications/Novel Contribution: The significance of this study lies in the fact that it uses media scanning, one of the most effective methods in the development of hate speech within the scope of research on hate speech in the national media, to bring attention to the separatist rhetoric and xenophobia used by individuals or communities who are the objects of hate speech. If we want to create a sustainable society based on fairness and equality, the language used in the media is crucial.